2009
DOI: 10.3892/or_00000521
|View full text |Cite
|
Sign up to set email alerts
|

American ginseng berry enhances chemopreventive effect of 5-FU on human colorectal cancer cells

Abstract: Abstract. In this study, we investigated the possible synergistic chemopreventive effects of American ginseng berry extract (AGBE) and 5-fluorouracil (5-FU) on human colorectal cancer cell lines, SW-480, HCT-116 and HT-29. We used high-performance liquid chromatography to determine the contents of major ginsenosides, the active components of American ginseng, in AGBE. The antiproliferative effects were evaluated by the cell counting method. AGBE (0.1-1.0 mg/ml) significantly inhibited SW-480, HCT-116 and HT-29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Our previous studies revealed that IFN-α inhibited HCC and extended the lifespan of mice and could be attributed to anti-angiogenesis [14,16]; SYY directly down-regulated MMP2 and VEGF and inhibited HCC growth and metastasis [15]. Others also reported that herbal medicine could inhibit the growth of MHCC97H cells used in this study [27] and could inhibit the invasiveness potential of HCC cells via MMP2 inhibition [28]. Based on our in vitro and in vivo studies, we considered that inhibition of the metastasis-enhancing effects due to dysregulation of MMP2/TIMP2 and VEGF might further improve operative efficacy in patients with HCC.…”
Section: Discussionmentioning
confidence: 84%
“…Our previous studies revealed that IFN-α inhibited HCC and extended the lifespan of mice and could be attributed to anti-angiogenesis [14,16]; SYY directly down-regulated MMP2 and VEGF and inhibited HCC growth and metastasis [15]. Others also reported that herbal medicine could inhibit the growth of MHCC97H cells used in this study [27] and could inhibit the invasiveness potential of HCC cells via MMP2 inhibition [28]. Based on our in vitro and in vivo studies, we considered that inhibition of the metastasis-enhancing effects due to dysregulation of MMP2/TIMP2 and VEGF might further improve operative efficacy in patients with HCC.…”
Section: Discussionmentioning
confidence: 84%